Integration of Islamic Values In Thermochemistry Teaching Materials For Grade XI SMA/MA - Krisandini, Triana; Mulia, Kristina (ALOTROP, 2025)
This study aims to produce chemistry teaching materials for Thermochemistry that contain Islamic values. The development of teaching materials was carried out using the Four Steps Teaching Material Development (4STMD) method. This study focuses on the Design and Development stages. The results of the teaching material development at the Design stage produce a teaching material design. The Development stage in developing teaching materials uses the Four Steps Teaching Material Development (4STMD) method, which consists of four stages: selection, structuring, characterization, and didactic reduction. The first stage begins with a selection process that produces 11 competency achievement indicators and 18 concept labels that must be developed. In the source selection step, 2 international textbooks and 1 high school textbook were used. The results obtained at the structuring stage are concept maps; macro structures and three levels of representation that are in accordance with the context of daily life and Islamic values. Characterization was carried out by 30 high school students and it was found that 4 texts were included in the difficult to understand category so that didactic reduction was carried out. The results of the didactic reduction stage were texts that were difficult for students to understand were given treatment with a type of didactic reduction back to the qualitative and neglect stages. The conclusion obtained from the results of this development research was the formation of chemistry teaching materials for Thermochemistry material that integrated Islamic values.